Molecular analysis of human and archaeal DNA repair helicases HelQ and Hel308 - Northall, Sarah (2017)
Completion of genome duplication by DNA replication catalyzed at stable replisomes is essential for life by facilitating cell division. Replisomes encounter physical blockage and chemical damage to DNA that frequently threatens to derail replication by inhibiting replisome enzymes. Multiple systems support DNA replication, by detection and repair of DNA damage and removal of physical blocks. Homologous recombination (HR) is one example. Archaeal Hel308 and metazoan HelQ DNA helicases are implicated in DNA repair by HR, in response to toxic DNA interstrand crosslinks that block replication forks. HelQ and Hel308 are single-strand DNA (ssDNA) stimulated ATPases with 3’ to 5’ translocase/helicase activity, most effective at unwinding forked DNA. Their helicase activities are likely to be crucial for promoting DNA replication and repair, but little is known about how. Here, I have been able to generate high yields of highly active human HelQ protein, compared to previous published strategies, and used in vitro biochemistry to show multiple oligomeric states of HelQ that are sensitive to reducing agents. I show that HelQ preferentially targets branched DNA molecules for DNA unwinding similarly to existing data for archaeal Hel308. HelQ and Hel308 demonstrated conservation of function between HelQ and archaeal Hel308 in winged helix domains of both proteins that led to a model for bi-modal DNA binding. This highlights how archaeal Hel308 may also be used as a model for HelQ function.